One-pot synthesis of multifunctional graphitic carbon-metal oxide nanocomposite for photocatalytic water purification and supercapacitor applications. Issue 21 (1st November 2021) - Shankar, Edugulla Girija; Billa, Sanjeev; Kumar, A.B.V. Kiran; Yu, Jae Su
Abstract: Multifunctional nanomaterials are emerging as potential materials with a wide variety of applications. Herein, we reported the one-pot facile synthesis of multifunctional graphitic carbon (gC)-CuO-ZnO nanocomposite for various applications of photocatalytic water purification, water disinfection, and supercapacitor electrode. The prepared gC-CuO-ZnO nanocomposite was characterized using microscopic and X-ray analysis techniques. Primarily, the synchrotron soft X-ray absorption spectroscopy studies were performed to investigate the internal environment of the nanocomposite using O K-edge, C K-edge, Zn L-edge, and Cu L-edge. The energy bandgap of the gC-CuO-ZnO nanocomposite was estimated to be 2.97 eV from the Tauc plot using ultraviolet–visible absorption spectra. In this regard, the prepared nanocomposite revealed excellent photocatalytic degradation against pharmaceutical compound amoxicillin and clavulanate potassium tablet, textile industrial effluent, and methylene blue dye under direct sunlight, indicating the efficiencies of 49 %, 89 %, and 97 %, respectively. Anti-microbial studies were performed against multidrug-resistant Escherichia fergusonii (MDR) strain using the gC-CuO-ZnO nanocomposites with different weight% of 1 %, 2 %, and 3 % and the obtained inhibition values were 16, 17.3, and 17.3 mm, respectively. Also, the gC-CuO-ZnO nanocomposite was employed as an electrode material of supercapacitors in energy storage applications. The gC-CuO-ZnO nanocomposite electrode exhibited excellent electrochemical properties, exhibiting the specific capacitance of 1102 F g -1 at 1 A g -1 . Consequently, the heterojunction nanocomposite via a facile one-pot synthesis was successfully employed for degradation of industrial effluents, toxicity against MDR bacteria, and an efficient supercapacitor electrode.